Prognosis for advanced-stage primary peritoneal serous papillary carcinoma and serous ovarian cancer in Taiwan - Kuan-Chong Chao; Yi-Jen Chen; Chi-Mou Juang; Hei-Yu Lau; Kuo-Chang Wen; Pi-Lin Sung; Feng-Ying Fang; Nae-Fang Twu; Ming-Shyen Yen (Elsevier, 2013)
Objective: To compare the prognosis of patients with advanced-stage primary peritoneal serous papillary carcinoma (PSPC) or papillary serous ovarian cancer (PSOC). Materials and Methods: This was a retrospective case-control study and included two study groups: one with stage III/IV PSPC (n = 38) patients and the other with PSOC (n = 53) patients. Patients were matched for histologic subtype (serous tumor), tumor stage, tumor grade, residual disease at the end of debulking surgery (primary or interval), and age (±5 years). Results: Mean age was significantly greater for patients with PSPC (63.03 ± 11.88 years) than for patients with PSOC (55.92 ± 12.56 years, p = 0.008). Optimal debulking surgery was performed initially in 71.9% of PSPC patients and 66.0% of PSOC patients. In addition, 93.9% of PSPC patients and 92.3% of PSOC patients were treated with platinum-paclitaxel chemotherapy. The frequency of high-grade tumors was significantly higher in the PSPC (100%) than in the PSOC group (68.3%; p < 0.001). Progression-free survival (PFS) was similar in the PSPC [median 12 months, 95% confidence interval (CI) 7.3-16.7] and PSOC groups (median 16.7 months, 95% CI 12.9-20.4; p = 0.470). Overall survival was shorter in the PSPC (median 62 months, 95% CI 19.6-104.4) than in the PSOC group (median 77.5 months, 95% CI 69.7-85.2; p = 0.006, log-rank statistic). Conclusion: PFS was similar for advanced-stage PSPC and PSOC patients. Since the PSPC patients tended to be older and have more high-grade tumors, OS was shorter for PSPC than for POSC patients. Thus, management of the two types of cancer should not differ.